Cellular aging -Alzheimer - Cuadrao Zavalela, Luis (2005)
Histoncally, The term illness of Alzheimer was used if the suffering began befare the 65 years of age, and senile insanity if he/she made it la ter. Nevertheless at the present time, illness of Alzheimer refers to insanity related with the independent changes characteristic anatomopatológics of the principle age. The . macroscopic exam of the brain Shows expansion of the cerebral furrows, in general more marked in the regions frontal and storm. The important microscopic characteristics of the Alzheimer illness are masses neurofibrilars, senile badges, degeneration granulovacuolar and bodies of Hirano.